New insights into photosynthetic oscillations revealed by two-dimensional microscopic measurements of chlorophyll fluorescence kinetics in intact leaves and isolated protoplasts - Ferimazova, Naila; Küpper, Hendrik; Nedbal, Ladislav; Trtílek, Martin (Photochemistry and photobiology, 2002)
Chlorophyll fluorescence kinetic microscopy was used to analyze photosynthetic oscillations in individual cells of leaves and in isolated leaf cell protoplasts. Four Brassicaceae species were used: Arabidopsis halleri (L.) O'Kane & Al-Shehbaz, Thlaspi fendleri (Nels.) Hitchc, Thlaspi caerulescens J.&C. Presl and Thlaspi ochroleucum Boiss et Helder. With the latter two, the measurements were extended also to isolated protoplasts. The oscillations were induced under the microscope by exposing dark-adapted samples to actinic irradiance. Detailed analysis of the induced transients revealed that they consist of several processes oscillating with different frequencies and not only one component as reported earlier. Furthermore, it was found that most of these processes are controlled inside each individual cell. This was shown by differences in oscillations in neighboring cells and protoplasts that share a uniform intercellular environment. The frequency of the dominant oscillation frequency depended neither on irradiance nor on CO2 concentration and is, therefore, not controlled by the photosynthetic rate. Characteristic differences in the frequency spectrum and damping of oscillations have been found among the plant species examined.
Keywords: fluorescence; Protoplasts; chlorofyl; Cells, Cultured; Fluorescence; listy rostlin; Kinetics; Photosynthesis; Brassicaceae; Microscopy, Fluorescence; Chlorophyll; Plant Leaves; protoplasty; kinetika; fotosyntéza; kultivované buňky; fluorescenční mikroskopie